2016
DOI: 10.1016/j.ridd.2015.11.023
|View full text |Cite
|
Sign up to set email alerts
|

The psychophysiological impact of childhood autism spectrum disorder on siblings

Abstract: Objective: The negative impact of caring for a child with autism spectrum disorder (ASD) on parents' psychophysiological functioning has been widely evidenced. However, siblings, who also face emotional, social and physical challenges associated with having a brother/sister with ASD, have been less widely studied. This study examined the psychophysiological impact of childhood ASD on Siblings of children with ASD experience greater emotional problems and overall depressive symptoms compared with a control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 69 publications
7
43
0
7
Order By: Relevance
“…There is an unmet need for greater sibling support. Where more support is available, particularly from family and close friends, siblings are less likely to succumb to psychological maladjustment (Barrera et al, 2004;Lovell and Wetherell, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is an unmet need for greater sibling support. Where more support is available, particularly from family and close friends, siblings are less likely to succumb to psychological maladjustment (Barrera et al, 2004;Lovell and Wetherell, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the experiences of parents and typically developing (TD) siblings (hereafter, just "siblings"), and the strategies they use to adjust to having a child with autism in the family are different (Lovell & Wetherell, 2016;McHale, et al, 2016;Vasilopoulou & Nisbet, 2016). For example, while parents may focus on how to improve their child with autism's abilities, siblings may care more about the behaviour of their brother or sister with autism which makes them feel embarrassed (Lock & Finstein, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Though the negative impact of maladaptive behaviors in youth with IDD on their typically developing (TD) siblings has been less widely studied, research has also shown that child problem behaviors do affect the well-being in siblings of children with IDD [48][49][50]. Interestingly, in Neece et al [50], mothers and fathers reported that their TD siblings were negatively impacted by the child with IDD (assessed at ages 5 through 8), more so than a control sample of TD children and their TD siblings.…”
Section: Impact Of Child Characteristicsmentioning
confidence: 99%